Kiina maailmantaloudessa: Globaalitalouden kasvu ja teollisen työnjaon muutos - Paavo Suni (The Research Institute of the Finnish Economy (ETLA), 2000)
– China is still a poor developing country. Since 1978, when the economy started to move in a more market-oriented direction, China has grown to become an influential player in the global economy. China has actively aimed to take part in the international division of labour. For example, in 2002 it became a member of the World Trade Organization (WTO). China's foreign trade has also increased substantially. With a share of goods and services exports in GDP of 29.5% in 2002, China is exceptionally open for a large economy according to the World Bank. China's active participation in the international division of labour fosters reallocation of global production, as enterprises optimise the geographic location of their production in this new environment. China's large labour reserves will ensure a competitive labour force for a long time to come, helping to make the country even more attractive as a destination for manufacturing activity in particular. In order to benefit from this change in the basic international economic setting, industrialised countries' production structures will have to shift towards higher value-added production.
Keywords: 330; International division of labour; China; global economy